Impact of crystalline orientation of lead-free solder joints on thermomechanical response and reliability of ball grid array components. (November 2020) - Ben Romdhane, E.; Guédon-Gracia, A.; Pin, S.; Roumanille, P.; Frémont, H.
Abstract: The microstructure of lead-free solder joints often consists of only one or a few randomly oriented tin grains as a result of cooling conditions and reactions that take place during the solidification. Due to severe anisotropy of the tin phase and this complex microstructure, the stress state of each joint will be unique, and lead to a dispersion in times to fail. This study aims at evaluating the impact of orientations of tin grains on the stress state of a BGA component. Different combinations of solder joint grain orientations are studied through thermo-mechanical simulations in order to assess the stress state of each joint. A significant effect of neighbouring joints has been observed for the different cases. Highlights: Thermomechanical response of lead-free solder joints is impacted by their as-reflowed microstructure. Finite Element results showed that the microstructure of solder joints needs to be considered in lifetime prediction model. Random Tin orientations in SAC solder joints can cause dispersion of times to failure.